Experimental and analytical investigation on frost heave characteristics of coarse-grained soils under closed and open systems - Huang, Wanjun; Mao, Xuesong; Wu, Qian; Zhao, Shichen; Zhang, Jianxun (Frontiers in Earth Science, 2022)
Coarse-grained soil is widely used in the seasonal frozen soil region as subgrade filler. However, substantial frost heave has been observed in coarse filler in high-speed railway embankments. To investigate the frost heave characteristics of the coarse-grained soil in a deep seasonal frozen soil zone, indoor tests were carried out under water supply and no water supply conditions. The effect of water, fineness, and temperature on frost heave behavior is studied experimentally. The relationship between the freezing rate and frost heave of coarse-grained soils was analyzed. The results show that the freezing process of the filler can be divided into the rapid cooling stage, phase transition stage, slow freezing stage, and freezing stability stage. In the closed system, the increase of the fine-grained soil does not affect the cooling process, while the moisture content significantly affects the whole process. In the opened system, both the fine-grained soil content and the ambient temperature affect the cooling process. When the ambient temperature decreased from −5°C to −15°C, the duration of the phase transition stage decreased by almost 17 h, whereas when the fine-grained soil content increased from 2.7 to 16%, the duration of the phase transition stage increased by only 5 h. In both opened and closed systems, the development of the frost heave is closely related to the cooling process. Approximately 95% of frost heave occurs during the phase transition stage and slow freezing stage. Frost heave develops most rapidly in the phase transition stage, with approximately 85% of the frost heave amount occurring in this stage.